What were the historical reasons for the resistance to recognizing airborne transmission during the COVID‐19 pandemic?. (21st August 2022) - Jimenez, Jose L.; Marr, Linsey C.; Randall, Katherine; Ewing, Edward Thomas; Tufekci, Zeynep; Greenhalgh, Trish; Tellier, Raymond; Tang, Julian W.; Li, Yuguo; Morawska, Lidia; Mesiano‐Crookston, Jonathan; Fisman, David; et al.
Abstract: The question of whether SARS‐CoV‐2 is mainly transmitted by droplets or aerosols has been highly controversial. We sought to explain this controversy through a historical analysis of transmission research in other diseases. For most of human history, the dominant paradigm was that many diseases were carried by the air, often over long distances and in a phantasmagorical way. This miasmatic paradigm was challenged in the mid to late 19th century with the rise of germ theory, and as diseases such as cholera, puerperal fever, and malaria were found to actually transmit in other ways. Motivated by his views on the importance of contact/droplet infection, and the resistance he encountered from the remaining influence of miasma theory, prominent public health official Charles Chapin in 1910 helped initiate a successful paradigm shift, deeming airborne transmission most unlikely. This new paradigm became dominant. However, the lack of understanding of aerosols led to systematic errors in the interpretation of research evidence on transmission pathways. For the next five decades, airborne transmission was considered of negligible or minor importance for all major respiratory diseases, until a demonstration of airborne transmission of tuberculosis (which had been mistakenly thought to be transmitted by droplets) in 1962. The contact/droplet paradigm remained dominant, and only a few diseases were widely accepted as airborne before COVID‐19: those that were clearly transmitted to people not in the same room. The acceleration of interdisciplinary research inspired by the COVID‐19 pandemic has shown that airborne transmission is a major mode of transmission for this disease, and is likely to be significant for many respiratory infectious diseases.